How to meet the needs of adolescents living in foster homes in Shiraz - Monfared-hesam abadi M; Mehri F; Mohammadi R; Keshavarz H (Iran University of Medical Sciences, 1994)
Background & Aims: The relative health of people is possible to provide the proper environment for physical development and their talent. According to Several problems in the social life of unsupervised children , as a social group , how to meet their needs is essential to solve these problems . This study was conducted In order to examine how to meet the needs of adolescents living foster homes in Shiraz.   Materials and Methods : This field study was conducted on the100 adolescents 11-18 years old, living in foster homes in Shiraz. Data was collected using a questionnaire containing demographic, physical and psychosocial needs and analyzed using descriptive statistics and chi-square test . Results : According to The need for calories , Age group 14-11 years had severely deficient and this deficiency was more common in boys . Safety needs of the majority of the boys " always" and 51/9 percent of girls in aged 11-14 years and 48 percent of girls ages 18 to 15 years, " rarely" is reported . In both groups, significant differences were found between girls and boys (p =0/0001). Needs for love and belonging, a majority ( 82/5%) of boys and girls " always" is reported . The majority (50% ) boys " always" and 44 % of girls aged 14-11 years, " often" and 48 % of girls aged 18-15 years, " rarely" was reported to meet need of their confidence and There was a significant statistical difference Between girls and boys in the age group 18-15 years (p =0/0137) and age 14-11 years (p =0/0003) There . Conclusion : Considering the different roles of community health nurses, they should be mobilized by Administrators and health planners in order to Planning and delivery of health services in foster homes to take effective steps in Promoting community health.